Tuning the optoelectronic properties of hematite with rhodium doping for photoelectrochemical water splitting using density functional theory approach - Abdur Rauf (Nature Portfolio, 2021)
Abstract Hematite (Fe2O3) is one of the best candidates for photoelectrochemical water splitting due to its abundance and suitable bandgap. However, its efficiency is mostly impeded due to the intrinsically low conductivity and poor light absorption. In this study, we targeted this intrinsic behavior to investigate the thermodynamic stability, photoconductivity and optical properties of rhodium doped hematite using density functional theory. The calculated formation energy of pristine and rhodium doped hematite was − 4.47 eV and − 5.34 eV respectively, suggesting that the doped material is thermodynamically more stable. The DFT results established that the bandgap of doped hematite narrowed down to the lower edge (1.61 eV) in the visible region which enhanced the optical absorption and photoconductivity of the material. Moreover, doped hematite has the ability to absorb a broad spectrum (250–800) nm. The enhanced optical absorption boosted the photocurrent and incident photon to current efficiency. The calculated results also showed that the incorporation of rhodium in hematite induced a redshift in optical properties.